Structural and optical properties of CaTiO3 perovskite-based materials obtained by microwave-assisted hydrothermal synthesis: An experimental and theoretical insight - Moreira, Mario L.; Paris, Elaine C.; do Nascimento, Gabriela S.; Longo, Valeria M. [UNESP]; Sambrano, Julio R. [UNESP]; Mastelaro, Valmor R.; Bernardi, Maria I. B.; Andres, Juan; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
CaTiO3 powders were synthesized using both a polymeric precursor method (CTref) and a microwave-assisted hydrothermal (CTHTMW) method in order to compare the chemical and physical properties of the perovskite-based material as a function of the synthesis method. To this end, X-ray diffraction, Raman spectroscopy, inductively coupled plasma atomic emission spectroscopy and experimental Ti and Ca K-edge X-ray absorption near-edge structure spectroscopy, as well as measurements of photoluminescence (PL) emission, were used to characterize the typical bottom-up process of the CaTiO3 perovskite phase at different times. Detailed Rietveld refinements show a random polycrystalline distortion in the powder structure, which can be associated with the tilting (alpha angle < O-Ti-O) between adjacent TiO6 octahedra (intermediate range) for CTHTMW samples and an intrinsic TiO6 distortion (short range) in relation to the polymeric precursor CTref sample. These properties were further investigated by first-principles calculations based on the density functional theory at the B3LYP level. The relationship between this tilting on the PL profile is highlighted and discussed. Thus, a structural model derived from both experimental results and theoretical simulations reveals a close relationship between this tilting and the presence of intermediate energy states within the band gap which are mainly responsible for PL emissions. (C) 2009 Published by Elsevier Ltd. on behalf of Acta Materialia Inc.
Keywords: CaTiO3; Microwave-assisted hydrothermal; Rietveld; Photoluminescence; Ab initio calculation